Anticancer Activity of Lectin Extracted from the Saltpan Microalga, Navicula sp. - Anithavani , Murugan; Rajan , Rayappan Anantha; Babu , Mariavincent Michael (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Haemagglutinins are carbohydrates binding protein applied as tools in cell biology and immunology. In the present study, lectin from selected microalgae Navicula sp. was isolated and characterized for biomedical applications. The microalgae were collected from the saltpan water sample. A total of six species were isolated including Amphora sp., Nitzschia sp., Navicula sp., Scendesmus sp., Chlorella sp. and Nanochloropsis sp. by direct plating method using algal isolation medium and characterized. The crude microalgal extracts were screened for the presence of lectin and it was confirmed by haemagglution assay. Among the strains, Navicula sp. showed potent haemagglutinin activity. Heamagglutinin from Navicula sp. was further partially characterized using chromatography methods. Navicula lectin agglutinated animal and human erythrocytes. It showed high specificity for human “O” erythrocytes with the titre value of 32 HA units. The HA activity was stable between pH 7and 8 and showed thermal stability between 30 ºC and 40 ºC (p<0.01). The isolated lectin was calcium dependent and HA activity was reduced when exposed to chelators such as EDTA (p<0.01). Hemagglutination inhibition assay exhibited the strongest binding specificity towards glucose, sucrose and galactose. The cross-adsorption assay revealed that the Navicula sp. Possesses single agglutinin. The purified lectin showed anticancer activity against cervical cancer cell lines.